Strategi Pengembangan Wisata Sungai Pingit di Desa Purbahayu, Kecamatan Pangandaran, Kabupaten Pangandaran, Jawa Barat - Syahrani Chantika Pratiwi; Atih Rohaeti Dariah (Bandung Conference Series: Economics Studies, 2024)
Abstract. The Pingit Rivers in Purbahayu Village, Pangandaran District, Pangandaran Regency, West Java Province is a natural object that has the potential to be developed into one of the characteristics of village tourism in Purbahayu. This research aims to find out the actual conditions of the Pingit Rivers tourist attractions through the 5A perspective (Attractions, Amenities, Activities, Accommodation and Accessibility) using value chain analysis as a basis for thinking about detailed tourist attraction development strategies. This research uses a descriptive qualitative approach, with primary and secondary data with interviews, observations and documentation obtained. The results of this research produced several strategies, namely 1) Strategy related to attractions by promoting tourist attractions through social media, print media, and strategic meeting forums between agencies. Collaboration with travel agents so that the Pingit Rivers is included in the tour packages. Facilitate training in developing community capacity in managing tourism promotional media. 2) Strategy related to amenities, namely improving the quality of prayer rooms, toilets and rinse rooms. 3) Strategy related to activities by offering tour packages in the form of swimming, fishing, using hammock, take photos at the terraced rock wall spot along with security guarantees. 4) Strategy related to accommodation, namely creating leisure facilities. Promoting processed food and drinks typical of Purbahayu Village through print media and social media, as well as facilitating training on processing, packaging, branding and product marketing. 5) Strategies related to accessibility, namely improving road access to tourist locations and completing information on signs and maps of tourist locations. Abstrak. Sungai Pingit di Desa Purbahayu, Kecamatan Pangandaran, Kabupaten Pangandaran, Provinsi Jawa Barat adalah objek alam yang berpotensi untuk dikembangkan menjadi salah satu ciri khas wisata desa. Tujuan dari penelitian ini adalah untuk mengetahui gambaran aktual dari objek wisata Sungai Pingit di Desa Purbahayu melalui perspektif 5A (Atraksi, Amenitas, Aktivitas, Akomodasi, dan Aksesibilitas) dengan menggunakan analisis rantai nilai sebagai landasan berpikir untuk mendetailkan strategi pengembangan objek wisata. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan jenis data yang digunakan terdiri dari data primer (wawancara, observasi, dokumentasi) dan sekunder yang diperoleh melalui informan kunci. Hasil penelitian ini menghasilkan beberapa strategi yaitu 1) Strategi terkait atraksi melakukan promosi daya tarik wisata melalui media sosial, media cetak, dan forum-forum pertemuan strategis antar instansi. Kerjasama dengan pihak agen perjalanan agar Sungai Pingit masuk bagian paket wisata. Melakukan fasilitasi pelatihan dalam pengembangan kapasitas masyarakat dalam pengelolaan media promosi wisata. 2) Strategi terkait amenitas yaitu meningkatkan kualitas sarana mushola, wc, dan kamar bilas. 3) Strategi terkait aktivitas dengan menawarkan paket wisata berupa aktivitas berenang, memancing, bersantai di tepian Sungai Pingit, berfoto pada spot dinding batuan berundak disertai jaminan keamanan. 4) Strategi terkait akomodasi yaitu pembuatan fasilitas bersantai. Mempromosikan makanan dan minuman olahan khas Desa Purbahayu melalui media cetak dan media sosial, serta fasilitasi pelatihan pengolahan, pengemasan, branding, dan pemasaran produk. 5) Strategi terkait aksesibilitas yaitu memperbaiki akses jalan menuju lokasi wisata serta melengkapi informasi rambu-rambu maupun peta lokasi wisata.